Anti-crisis personnel management in the process of ensuring the economic security of the enterprise - Stepan Melnyk; Natalia Shuprudko; Iryna Kolosovska; Ihor Berest; Mykhaylo Pasichnyk (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Crisis phenomena in many countries of the world do not allow enterprises to develop. Enterprises have to face permanent threats and risks that significantly reduce the current level of their economic security, the problem of creating a protection system, that is, an integrated system of economic security has become a priority. The aim of the article is to determine the impact of the crisis on the management process and the efficiency of personnel use as the basis for the development of anti-crisis solutions, the implementation of which should provide the necessary level of economic security for the enterprise. The results of our study allowed us to identify possible options that ensure the effective implementation of anti-crisis personnel management, focused on restoring the level of economic security necessary for the functioning and development of the enterprise. It was found that in the process of implementing anti-crisis personnel management it has a number of features caused by both the difference in the impact of the crisis, that is, the presence of positive and negative consequences, and a significant list of external and internal factors that must be taken into account when developing each individual anti-crisis solution.
Keywords: C50; M12; M30; M21; 650; anti-crisis management; personnel management; economic security; enterprise; security